Christianity, ‘supernatural’ beliefs and COVID-19 - E. Shoko (Acta Theologica)
COVID-19 arguably had far-reaching implications for Christianity and the church as an institution. Issues around social distancing and lockdown directly impacted articulation and religious expression, while understanding of the pandemic and the virus were mediated through constructions of religio-spiritual beliefs. Given this, the study sought to explore some neo-Pentecostal church leaders’ messages in South Africa regarding the novel coronavirus or COVID-19, what this meant to their followers and the associated implications for the spread and effects of COVID-19. Methodologically, the researcher iewed and listened to uploaded YouTube video clips of news related to the church and COVID-19, uploaded by media outlets and the neo-Pentecostal church leaders themselves as well as online newspaper reports from the period 2 March to 19 June 2020. The findings of the study reveal that neo-Pentecostal church leaders attributed the origins of SARS-COV-2 to “evil” spirits. Neo-Pentecostal church leaders had mixed messages on the possible cure for COVID-19, with some emphasising miracles as the panacea for COVID-19, and a minority believing that God exhibits his power through epidemiologists. Prayer was also viewed as a tool for Christians to protect themselves from contracting COVID-19 through the invocation of divine powers. The paper concludes that the pervasive influence of church leaders and their emphasis on spiritual remedies such as prayer and miracles may have given Pentecostal followers a false sense of security, which might have affected their awareness of COVID-19.